The Impact of Islamic Stock Market Capitalization on the Growth of Islamic Mutual Funds in Indonesia: A Time Series Analysis (2011–2025): Pengaruh Kapitalisasi Pasar Saham Syariah terhadap Pertumbuhan Reksa Dana Syariah di Indonesia: Analisis Deret Waktu (2011–2025) - Ahyak; Sulhan (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2025)
This study investigates the causal relationship between Islamic stock market capitalization and the growth of Islamic mutual funds in Indonesia during the 2011–2025 period. Despite the rapid expansion of Islamic finance, empirical insights into the interdependence between its key pillars—Islamic equity markets and Islamic mutual funds—remain limited. Using annual data from the Financial Services Authority (OJK), this study applies a time series analysis using the Vector Autoregression (VAR) model on first-differenced data. The analysis is preceded by stationarity tests (Augmented Dickey-Fuller and KPSS) and optimal lag selection.The variables analyzed include the logarithm of the Net Asset Value (NAV) of Islamic mutual funds and the logarithm of the Jakarta Islamic Index (JII) as a proxy for Islamic stock market capitalization. Findings reveal that both variables are non-stationary at level but become stationary after first differencing. Granger Causality tests, Impulse Response Functions (IRFs), and Variance Decomposition (VDC) consistently indicate no significant bidirectional causal relationship between the two variables.These results suggest that the two segments tend to move relatively independently within the observed period. The study contributes by providing recent empirical evidence and offers practical implications for regulators, fund managers, and investors in formulating more integrated and sustainable Islamic capital market development strategies.